Performance-based financing as a health system reform: mapping the key dimensions for monitoring and evaluation - Witter, Sophie (BioMed Central, 2013)
BACKGROUND: Performance-based financing is increasingly being applied in a variety of contexts, with the expectation that it can improve the performance of health systems. However, while there is a growing literature on implementation issues and effects on outputs, there has been relatively little focus on interactions between PBF and health systems and how these should be studied. This paper aims to contribute to filling that gap by developing a framework for assessing the interactions between PBF and health systems, focusing on low and middle income countries. In doing so, it elaborates a general framework for monitoring and evaluating health system reforms in general. METHODS: This paper is based on an exploratory literature review and on the work of a group of academics and PBF practitioners. The group developed ideas for the monitoring and evaluation framework through exchange of emails and working documents. Ideas were further refined through discussion at the Health Systems Research symposium in Beijing in October 2012, through comments from members of the online PBF Community of Practice and Beijing participants, and through discussion with PBF experts in Bergen in June 2013. RESULTS: The paper starts with a discussion of definitions, to clarify the core concept of PBF and how the different terms are used. It then develops a framework for monitoring its interactions with the health system, structured around five domains of context, the development process, design, implementation and effects. Some of the key questions for monitoring and evaluation are highlighted, and a systematic approach to monitoring effects proposed, structured according to the health system pillars, but also according to inputs, processes and outputs. CONCLUSIONS: The paper lays out a broad framework within which indicators can be prioritised for monitoring and evaluation of PBF or other health system reforms. It highlights the dynamic linkages between the domains and the different pillars. All of these are also framed within inter-sectoral and wider societal contexts. It highlights the importance of differentiating short term and long term effects, and also effects (intended and unintended) at different levels of the health system, and for different sectors and areas of the country. Outstanding work will include using and refining the framework and agreeing on the most important hypotheses to test using it, in relation to PBF but also other purchasing and provider payment reforms, as well as appropriate research methods to use for this task.